The Effect of Learning Achievement on Schadenfreude with Self Esteem Mediation on Students of SMAN 1 Kebomas Grade Eleven - Kusmantoro, Rapaela; Rahayuningsih, Idha (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2023)
This study aims to determine the effect of learning achievement on schadenfreude by mediating self-esteem in 11th grade students of SMA N 1 Kebomas. This study used a quantitative approach using incidental sampling technique and obtained 86 samples of 11th grade students from 243 students. The method of collecting data for the Schadenfreude and self-esteem variables was using a Likert scale and the learning achievement variable was using report cards. The scale validity test uses content validity and the scale reliability test uses Cronbach's Alpha technique. Hypothesis test using simple linear regression technique and mediation analysis test using JASP For Windows mediation analysis test. The results of this study indicate that the significant value of the self-esteem variable with the Schadenfreude variable is 0.004 < 0.05, then Ho is rejected and Ha is accepted, which means the effect of self-esteem on Schadenfreude is 30.7%, while for the learning achievement variable with the self-esteem variable, it is 0.288> 0.05 then Ho is accepted and Ha is rejected, which means there is no effect, then the significant value of the learning achievement variable and Schadenfreude is 0.734 > 0.05 then Ho is accepted and Ha is rejected, which means there is no effect, and the last significant value of the learning achievement variable on Schadenfreude with self-esteem mediation of 0.159 > 0.05 then Ho is accepted and Ha is rejected, which means that there is no effect of learning achievement on Schadenfreude's attitude with self-esteem mediation. The data category from the Schadenfreude scale shows that the majority of the subjects are in the medium category, as many as 64 subjects with a percentage of 74%. The category of data from the self-esteem scale shows that the majority of subjects are in the medium category, as many as 63 subjects with a percentage of 73%. The data category on the learning achievement scale shows that the majority of the subjects are in the medium category, as many as 51 subjects with a percentage of 59%.